Analisis Manajemen Risiko Operasional berbasis ISO 31000:2018 terhadap Perusahaan Logistik: Studi Kasus JNE Station Center Gedebage Kota Bandung - Desi Ratna Haryanti; Mohamad Hutomo (Universitas Nusantara PGRI Kediri, 2024)
The logistics industry in Indonesia, including JNE Station Center Gedebage, Bandung City, is experiencing rapid development. This has consequences in the form of increased operational risk which results in a decrease in service quality and obstacles to achieving company goals. Operational risk is a natural thing in a company, but it would be better if the risk could be mitigated from the start so as not to have an undesirable impact. Therefore, the implementation of optimal risk management is important. In measuring operational risk, adequate and easy-to-implement guidelines are needed. The International Organization for Standardization (ISO) 31000:2018 is considered to be an adequate guideline. This study aims to analyze the company's operational risk management based on ISO 31000:2018 which consists of risk management principles and processes. A qualitative method with a case study approach was used to collect data, through interviews and document analysis. The results of the study indicate that JNE Station Center Gedebage, Bandung City implements operational risk management in accordance with the company's SOP based on ISO 9001:2015. The main operational risks identified are late delivery, damaged goods, and lost goods. In conclusion, JNE Station Center Gedebage has met the requirements of ISO 31000:2018 and is considered capable of implementing operational risk management principles and processes based on the ISO 31000:2018 standard.